Engaging transculturality
1 online resource.
Keywords: "Engaging Transculturality is an extensive and comprehensive survey of the rapidly developing field of transcultural studies. In this volume, the reflections of a large and interdisciplinary array of scholars have been brought together to provide an extensive source of regional and trans-regional competencies, and a systematic and critical discussion of the field's central methodological concepts and terms"--